GONADOSOMATIC INDEX AND FECUNDITY OF AN INDIAN MAJOR CARP LABEO CALBASU IN GOHAD RESERVOIR - SHAILJA MISHRA,; D. N. SAKSENA, (The Bioscan, 2012)
In the present study gonadosomatic index and fecundity of an Indian major carp Labeo calbasu in spawning season i.e. from May to August 2007 have been reported. Ovarian weight of the carp ranges from 140±320 g with a mean value of 201±16.56 g. The ovarian weight is almost 20% of the body weight in fully mature fishes. In this study, it has been shown that the fecundity of fish increase with the increase in size, weight of fish and gonad weight. The average weight and length of fish are 1006±75.22g and 38.85±1.29cm respectively. The average fecundity was measured as 402217±30661 ova per fish with an average fecundity of 400.5±8.40 ova per gram of body weight and 10241±401.8 ova per cm of fish length.